The effect of combination spirulina-chitosan on angiogenesis, osteoclast, and osteoblast cells in socket models of hyperglycemic Rattus norvegicus - Nike Hendrijantini; Rostiny Rostiny; Mefina Kuntjoro; Kent Sidharta; Dea Syarafina Putri Wiyono; Alocitta Anindyanari; Sherman Salim (Wolters Kluwer Medknow Publications, 2018)
Background: Prolongation of the inflammatory process in hyperglycemic interferes with bone formation, inhibits the healing process, and triggers bone resorption. A combination of spirulina and chitosan in the tooth socket of Rattus norvegicus is expected to promote the bone remodeling process. This study aimed to evaluate the effect of spirulina and chitosan on angiogenesis, osteoclast, and osteoblast cell in tooth socket models of type 1 diabetes. Materials and Methods: A laboratory-based experiment involving 36 R. norvegicus, divided into three groups (nondiabetes mellitus (DM), uncontrolled DM, and controlled DM) and further divided into six subgroups. The controlled groups (K1, K2, and K3) were induced with 3% carboxymethyl cellulose Na, while the treated groups were induced with 12% spirulina and 20% chitosan. On the 14th day, the mandibles of the rats were removed. The capillary lumen, osteoblasts, and osteoclast cells were counted by hypothalamic-pituitary-adrenal examination and the results analyzed by means of Shapiro-Wilk, Levene's, one-way ANOVA, and post hoc Tukey's honestly significant difference test. Results: There was a significant increment in the number of capillary lumen, osteoblast cells, and a decrease in osteoclasts in all three treated groups (P1, P2, and P3). Conclusions: A combination of spirulina and chitosan can effectively promote the healing process in postextraction sockets of type 1 DM R. norvegicus.